Effect of elevated high temperature stress on seed quality of Brassica rapa in ambient storage condition - Aradhana Phukan; R Das; RN Sarma; PK Barua (Journal of Oilseed Brassica, 2026)
In view of the current issue of high temperature stress on seed yield and quality, the present investigation was undertakento assess the effect of high temperature on seed viability of Brassica rapa during 2017-18 at Assam AgriculturalUniversity, Jorhat. Fifteen entries were grown under temperature gradient tunnel (stress) and in the open field (nonstress) conditions in randomized block design with two replications. Seed germination percentage and vigour index wereobserved on the seeds after nine months of storage. Significant variation was observed among the genotypes forgermination percentage in stress but not in non-stress condition. For seed vigour index, the genotypes, parents, crossesand parents vs. crosses significantly differed in both stress and non-stress environments. Germination declined by 12 %and seed vigour index by 223 under high temperature stress. Only in stress condition, significant variations for generalcombining ability (GCA) and specific combining ability (SCA) were observed for germination percentage. Seed vigourindex showed significant variations for GCA and SCA effects in both stress and non-stress conditions. Yellow sarsonparents exhibited better combining ability for seed quality after storage than the toria parents under high temperaturestress.